Editorial: Introduction to the special issue on English language learning in primary schools - del Pilar García Mayo, María; Gutierrez-Mangado, M. Juncal (Studies in Second Language Learning and Teaching, 2020)
The early introduction of foreign languages, mainly English, in pre-primary and primary education in different parts of the world is an undisputable fact in today’s world, as clearly illustrated in Enever (2018). One of the reasons for this educational change is the belief in “the earlier the better” notion, which has already been shown not to hold true when linguistic outcomes are assessed in foreign language settings (see García Mayo & García Lecumberri, 2003; Huang, 2015). Age is just one variable among many others that need to be taken into account when assessing child language learning in educational contexts (see Butler, 2019), and that is the reason why more research on identifying those other variables is necessary.